فعالية رقمنة القطاع الصحي في تحسين الخدمة الصحية: الملف الطبي الإلكتروني نموذجًا - بن عجمية, أميرة شيماء (كلية العلوم الاجتماعية, 2025)
تهدف هذه الدراسة إلى إعطاء نظرة حول واقع الرقمنة في القطاع الصحي و بالأخص الملف الإلكتروني الطبي ، و ما مدى مساهمة هذه الرقمنة في تحسين الخدمات الصحية . من أجل تحقيق هدف الدراسة،استخدمنا المنهج التحليلي الوصفي لتناسبه مع إشكالية الدراسة، و استخدمنا تقنية المقابلة والتي تدخل ضمن المنهج الكيفي وتوصلنا إلى جملة من نتائج أهمها : أن أغلبية أفراد العينة أجمعوا على أن المؤسسة الإستشفائية تعتمد على الرقمنة و في تطور ملحوظ، و ذلك من خلال إعتماد العديد من البوابات و المنصات الإلكترونية،هناك علاقة تأثير للرقمنة عالية المدى في تحسين الخدمة الصحية في المؤسسة محل الدراسة.بالإضافة إلى أن أنظمة المعلومات تعتبر قاعدة أساسية في تسيير المستشفى، بم في ذلك الملف الإلكتروني الطبيو أنه القائم على أعمال ورقية أقل و تخزين أكثر.هذا و تكمن فعالية الرقمنة في تنظيم سيرورة العمل و تسريع عملية تبادل المعلومات و التواصل. This study aims to provide an overview of the state of digitization in the healthcar sector, with a particular focus on the electronic medical record, and to examine the extentto which this digitization contributes to improving healthcare services. To achieve the study’s objective, we used the descriptive analytical method, as it aligns with the study's problem, and we employed the interview technique, which is part of the qualitative approach. The study led to several key findings, most notably: the majority of respondents confirmed that the healthcare institution relies on digitization and is witnessing significant development, through the use of various electronic portals and platforms. There is a strong correlation between digitization and the improvement of healthcare services at the institution under study. Furthermore, information systems are considered a fundamental foundation for hospital management, including the electronic medical record, which is based on reduced paperwork and increased data storage. The effectiveness of digitization lies in organizing workflows and accelerating the exchange of information and communication.
دراسة ميدانية في المؤسسة العمومية الاستشفائية بولاية غليزان
Keywords: الرقمنة ، الخدمة الصحية ، الملف الإلكتروني الطبي ،القطاع الصحي